Discovery of Ghrelin hormone: Research and clinical applications - Aydin, Sueleyman (Walter de Gruyter Gmbh, 2007)
Ghrelin, orexigenic hormone, is a recently discovered, growth hormone-releasing and feeding-stimulating peptide in human and animals. It was mainly produced in the stomach and also secreted from many other tissues (including parenchyma cell of plants), This hormone circulates in high levels in the bloodstream under fasting conditions and decreases with feeding. Ghrelin initiates meal, regulates appetite, energy expenditure and fuel utilization. In this review, it will be focused on the recent knowledge of ghrelin structure, history, function, distribution, alteration in diseases, and its possible clinical applications.
Keywords: Ghrelin; orexigenic hormone; appetite; growth hormone releasing